Conflict Management in the Operation of Trans Padang Corridor VI - Palzi, Palzi; Yuliarti, Yuliarti (Indonesian Journal Publisher, 2024)
Padang Mayor Regulation Number 127 of 2021 sets minimum service standards for the management, implementation, and service of Trans Padang public transportation. This research uses a qualitative research method with a descriptive method to find out how the Padang City government handles the demo conflict that occurred between Padang angkot drivers and Trans Padang drivers on the Trans Padang travel route in Corridor VI. This research uses a descriptive method because the research describes, tells, and interprets a situation or event as it is. The study investigated the location of the conflict, Corridor VI of Trans Padang, and asked the government and the Padang City Transportation Office about the people directly involved in the conflict between Trans Padang and Padang angkot drivers. The results show that conflict management in Trans Padang corridor 6 is not going well. The government and stakeholders should communicate more and work together to resolve this conflict. In addition, the government should consider the interests of the angkot drivers and find a solution that benefits all parties.